Prevalence of Dysmenorrhea and its Effects on Academic Performance among higher secondary Students” - Radha Paudel; Sarita Shrestha (Journal of Karnali Academy of Health Sciences, 2021)
Background: Dysmenorrhea is the most common complaint and leading cause of absenteeism in adolescence among university female students. It affects the social, academic and sports activities. Therefore, the objective of the study was to find out the prevalence of dysmenorrhea and its effects on academic performance among higher secondary students.